Analisis Kinerja Ekonomi Sektoral Di Kota Gorontalo - Fadliya Paputungan; Syarwani Canon; Sri Indriyani Dai (UNIVED Press, 2022)
This research was carried out in Gorontalo City and Gorontalo Province as a reference area. The research aimed to identify the sectoral economic performance both from contribution and growth rate as well as to determine the competitive and comparative advantages in Gorontalo City. The data used were time series GRDP (Gross Regional Domestic Product) data of Gorontalo and Gorontalo Province on the basis of constant prices from 2010 to 2020. At the same time, this research employed four analysis techniques, namely descriptive analysis, contribution analysis, LQshift Analysis, and LQshare analysis. The results of the descriptive analysis depicted that the electricity and gas procurement, financial services and insurance, information and communication sectors had higher growth compared to other sectors. Besides, contribution analysis indicated that the sectors of construction, wholesale and retail, car and motorcycle repair, government administration, defense and social security had contributions from other sectors. In the meantime, the LQshare analysis revealed that the sectors with specialization or comparative advantages were water supply, waste management, waste and recycling, real estate, financial services and insurance, accommodation, and food and beverage provision. LQshift analysis denoted that sectors with competitiveness or competitive advantages were the accommodation and food and beverage provision, water supply, waste management, waste and recycling, and information and communications sectors.